2021
DOI: 10.3390/cells10112824
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three CD3-Specific Separation Methods Leading to Labeled and Label-Free T Cells

Abstract: T cells are an essential part of the immune system. They determine the specificity of the immune response to foreign substances and, thus, help to protect the body from infections and cancer. Recently, T cells have gained much attention as promising tools in adoptive T cell transfer for cancer treatment. However, it is crucial not only for medical purposes but also for research to obtain T cells in large quantities, of high purity and functionality. To fulfill these criteria, efficient and robust isolation met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Our observation that macrophage-tropic mutations were incompletely associated with meninges-derived sequences could have resulted from mixed cell populations. On the other hand, the methodology we used here (positive cell selection using magnetic beads) has been assessed in previous studies that found >98% cell purity for both CD3 + ( 47 ) and CD14 + ( 48 , 49 ) populations, providing indirect support for the robustness of the method.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that macrophage-tropic mutations were incompletely associated with meninges-derived sequences could have resulted from mixed cell populations. On the other hand, the methodology we used here (positive cell selection using magnetic beads) has been assessed in previous studies that found >98% cell purity for both CD3 + ( 47 ) and CD14 + ( 48 , 49 ) populations, providing indirect support for the robustness of the method.…”
Section: Discussionmentioning
confidence: 99%
“…However, one feasible way to mitigate this T-cell misfunction is to isolate and expand the T-cell CD3+ fraction specifically [71]. Nowadays there are a variety of kits widely used that are designed to enrich solely this CD3+ fraction [72,73]. Studies such as that by Ji et al demonstrate that G-CSF priming did not change the total number of CD3+ cells in marrow grafts but decreased CD4+ cells and increased CD8+ cells, resulting in a significant reduction in CD4:CD8 ratio [74].…”
Section: Car-t Immunotherapymentioning
confidence: 99%
“…Considering the benefits previously mentioned and with the knowledge of the clinical success of T lymphocytes after mobilization [80][81][82] researchers have recently opened the debate about its utilization for purposes such as CAR-T cell production. In fact, it is not unreasonable to think that with the current sample processing and enrichment techniques, one could use a determined volume of the mobilized product to isolate solely the T-cell fraction without altering the functionality of these cells [72]. Some examples using a variety of cytokines and activation protocols for T-cells [85] can obtain different subpopulations.…”
Section: Car-t Immunotherapymentioning
confidence: 99%
“…Weiss et al carefully tested three commonly used methods for the isolation of CD3-specific T cells from human buffy coats and peripheral blood mononuclear cells (PBMCs) based on the rationale of either immune affinity chromatography or magnetic beads. They found all three methods to be highly efficient for isolating T cells, with a high viability (>92%) and purity (>98%) [ 2 ]. For the data analysis, Walbech et al implemented a deep learning framework of autoencoders to extract informative features from scRNA-seq data, as well as for further denoising and classification.…”
mentioning
confidence: 99%